Winter Hardiness and Freezing Tolerance in a Hairy Vetch Collection. Issue 4 (21st June 2018) - Wiering, Nicholas P.; Flavin, Claire; Sheaffer, Craig C.; Heineck, Garett C.; Sadok, Walid; Ehlke, Nancy J.
Abstract : Hairy vetch ( Vicia villosa Roth) is a winter‐annual legume that is grown as a cover crop and for forage. Although more winter tolerant than most leguminous winter annuals, it does not reliably overwinter in the upper Midwestern United States. Our objectives were to screen a collection of accessions for winter hardiness and develop a screening method for freezing tolerance in a controlled setting. We evaluated 30 accessions (commercial germplasm and breeding populations) in multiple Minnesota environments. Average winter survival among accessions ranged from 13 to 73% and resembled a bimodal distribution, where two distinct phenotypic groupings were apparent. Commercial VNS (variety‐not‐stated) accessions were found to be highly variable for winter survival. Seed derived from Minnesota was generally winter hardy (>65% survival), and seed from Oregon was not (<39%). Due to large variation among and within field environments, a method of controlled freezing was developed to supplement winter hardiness evaluations. No differences in freezing tolerance were found among accessions without cold acclimation. However, large differences in freezing tolerance occurred when plants were first grown for 2 wk in greenhouse conditions (22°C, 16‐h photoperiod) and then cold acclimated for 4 wk (3°C, 10‐h photoperiod). Lethal temperatures were determined from six 24‐h programmed freezing treatments, where treatment temperatures ranged from −13 to −21°C. Accessions differed significantly for freezing tolerance, with median lethal temperature values ranging from −8.4 to −16.0°C. This method of controlled freezing correlated highly with winter survival in field evaluations (ρ = 0.77).